Effect of Maternal Preeclampsia on the Weight of the Placenta - Kishwara, Segupta; Nurunnabi, Abu Sadat Mohammad; Begum, Mahamuda; Rayhan, Khandaker Abu; Ara, Shamim (Bangladesh Journal of Anatomy, 2011)
Context: Preeclampsia is a relatively common pregnancy disorder that is related to the placenta and causes variable maternal and foetal problems. Alterations in placental weight are evident in moderate to severe maternal preeclampsia. Study design: Cross-sectional descriptive type. Place and period of study: Department of Anatomy, Dhaka Medical College, Dhaka from August 2005 to June 2006. Materials & Methods: 60 human placentae from Bangladeshi women were collected from the Department of Obstetrics & Gynaecology of Dhaka Medical College Hospital and Mitford Hospital, Dhaka of which 30 from normal uncomplicated pregnancies (control group or group A) and another 30 from pregnancies complicated by preeclampsia (preeclampsia group or group B), where the patients were normotensive previously. Results: The mean weight of the placenta was 406.90±72.64 gm in control group (group A) and 311.50±74.09 gm in preeclampsia group (group B) respectively. The mean difference in weight between two groups was statistically significant (P< 0.001). Conclusion: Placental weight was found reduced in maternal preeclampsia in comparison to that of normal pregnancy. Key words: weight of placenta; preeclampsia. DOI: 10.3329/bja.v8i2.7019 Bangladesh Journal of Anatomy July 2010, Vol. 8 No. 2 pp. 69-71